The Analysis Study of Effects of Metformin on Ovarian Cancer : A Comprehensive Systematic Review - Fetana, Innesti Nur; Yoebel, Faisal (International Medical Journal Corp. Ltd, 2024)
Background: Ovarian cancer is one of the 10 most common cancers in women, with an estimated 295,414 new cases and 184,799 deaths worldwide in 2018. Metformin also activates the adenosine monophosphate-activated protein kinase pathway via liver kinase B1, which is a key gate pathway related to inhibition of subsequent tumor growth biomarkers, insulin signaling cascade, and cell cycle regulatory pathways. The aim: The aim of this study to show about effects of metformin on ovarian cancer. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Long-term metformin use reduced all-cause mortality, but not cancer-specific survival (CSS) in ovarian cancer. Whether metformin itself reduces deaths because of ovarian cancer requires further investigation.